A Novel Self-Assembled Gel for Gastric Endoscopic Submucosal Dissection-Induced Ulcer: A Preclinical Study in a Porcine Model - Meng Li; Haifeng Jin; Changpei Shi; Bin Lyu; Xiao Ying; Yuan Shi (Frontiers Media S.A., 2021)
Endoscopic submucosal dissection (ESD) is a routine procedure for the management of early gastrointestinal neoplasia, but it results in large ulcers. This study aims to examine the feasibility and effectiveness of a newly developed self-assembled gel on the ulcer healing process after ESD. Sixteen 2.0-cm (diameter) gastric ulcers were created by ESD in five pigs. All ulcers were randomized: control group (n = 7, routine ulcer management) and gel-treated group (n = 9). The gel was applied to cover the whole ulcer bed through the endoscope immediately after ESD. The feasibility of this endoscopic treatment modality was macroscopically accessed by endoscopy. The effectiveness was evaluated based on the ulcer area and histology changes at 14 days after ESD. The gel-treated group showed higher healing activity compared with the control ulcers on day 14 after ESD. The percentage of healing was higher for the gel-treated ulcers than in control ones (96.2 ± 2.2% vs. 91.9 ± 4.5%, p = 0.035). The extent of the new epithelium covering the ulcer was greater in the gel group than in controls. One delayed overt bleeding occurred in the control group (14.3%). This novel gel might promote the speed of ulcer healing after ESD, leading to higher epithelium formation.